Classification and mineralization of global lithium deposits and lithium extraction technologies for exogenetic lithium deposits - Mian-ping Zheng; En-yuan Xing; Xue-fei Zhang; Ming-ming Li; Dong Che; Ling-zhong Bu; Jia-huan Han; Chuan-yong Ye (China Geology)
A reasonable classification of deposits holds great significance for identifying prospecting targets and deploying exploration. The world’s keen demand for lithium resources has expedited the discovery of numerous novel lithium resources. Given the presence of varied classification criteria for lithium resources presently, this study further ascertained and classified the lithium resources according to their occurrence modes, obtaining 10 types and 5 subtypes of lithium deposits (resources) based on endogenetic and exogenetic factors. As indicated by surveys of Cenozoic exogenetic lithium deposits in China and abroad, the formation and distribution of the deposits are primarily determined by plate collision zones, their primary material sources are linked to the anatectic magmas in the deep oceanic crust, and they were formed primarily during the Miocene and Late Paleogene. The researchers ascertained that these deposits, especially those of the salt lake, geothermal, and volcanic deposit types, are formed by unique slightly acidic magmas, tend to migrate and accumulate toward low-lying areas, and display supernormal enrichment. However, the material sources of lithium deposits (resources) of the Neopaleozoic clay subtype and the deep brine type are yet to be further identified. Given the various types and complex origins of lithium deposits (resources), which were formed due to the interactions of multiple spheres, it is recommended that the mineralization of exogenetic lithium deposits (resources) be investigated by integrating tectono-geochemistry, paleoatmospheric circulation, and salinology. So far, industrialized lithium extraction is primarily achieved in lithium deposits of the salt lake, clay, and hard rock types. The lithium extraction employs different processes, with lithium extraction from salt lake-type lithium deposits proving the most energy-saving and cost-effective.©2023 China Geology Editorial Office.